Nature's Remedy: Exploring Herbal Treatments for Polycystic Ovarian Syndrome - Attri, Meenakshi; Raghav, Asha; Chaudhary, Hema (Current Nutraceuticals, 2024)
Polycystic Ovarian Syndrome (PCOS) is a complex condition characterized by chronic ovulation issues and hyperandrogenism, affecting approximately 6% to 20% of women of reproductive age, depending on diagnostic criteria. Symptoms typically manifest during early adolescence, presenting as irregular menstrual cycles, anovulation, and acne. While some mechanisms underlying PCOS development have been identified, its precise etiology and pathophysiology remain elusive.This article delves into the pathogenesis and management of PCOS by exploring relevant literature on PubMed. Various contributing factors to PCOS were meticulously examined, including epigenetics, environmental toxins, stress, diet, inflammation, oxidative stress, hyperandrogenism, insulin resistance, and obesity. This review examines the importance of herbal remedies in addressing Polycystic Ovarian Syndrome (PCOS), focusing on the chemical makeup, mode of action, and therapeutic uses of specific herbal medications targeting PCOS. However, despite this investigation, there remains a significant gap in completed clinical trials on repurposed drugs for PCOS, often with small sample sizes and inconclusive outcomes. Given the limited research in this area, further studies and carefully planned clinical trials are warranted to understand PCOS and its management better. Additionally, gaining deeper insights into PCOS could facilitate the development of novel drugs targeting newly discovered pathways, thereby improving treatment options for individuals affected by this syndrome.
Keywords: hyperandrogenism